863 views
0 votes
- 4x + 9y = 9
-8x + 10y = 10

2 Answers

7 votes

Answer:

(0,1)

x = 0

y = 1

Explanation:

(-4x + 9y = 9)-8

(-8x + 10y = 10)4

32x - 72y = -72

-32x + 40y = 40

-32y = -32

y= -32/-32

y=1

-4x + 9(1) = 9

-4x + 9 = 9

-4x = -9 + 9

-4x = 0

x = 0/-4

x = 0

User BrodieG
by
5.0k points
3 votes

Answer:

y = 1, x = 0

Explanation:

multiply -4x +9y = 9 by -2 to get 8x -18y = -18

combine the two equations to get -8y = -8

divide both sides by -8 to get y = 1

plug in 1 as the y into one of the equations and solve to get x = 0

User Mkl Rjv
by
5.3k points